The Organizational Context of Nursing Practice Concepts, Evidence, and Interventions for Improvement (Springer International Publishing, 2018)
This book explores the various features of work environments that affect nurses' experiences of their work, their interactions with co-workers and patients, and ultimately health care quality and patient outcomes. Using a broad and comprehensive approach, the authors identify the most extensively researched and best-understood concepts in the field and presents a critical and up-to-date review of the evidence regarding causes and effects of work environment features. It then presents evidence regarding organizational interventions aimed at broad ranges of clinical practices and outcomes, such as team-based interventions and management practices to improve practice climate. The ideas, approaches, and evidence are presented by a team of researchers and experienced practitioner/leaders; taken together, they form a state-of-the-science toolkit. Unique features of this book include a systematic presentation of best practices in nursing and healthcare leadership, along with the conceptual grounding and empirical support for these approaches, and extensive demonstrations of how these practices, many of which originated in North America, apply to European contexts. .